Coping Mechanism and Resilience Strategies of Nurses in the Provincial Government of Albay: Strengthening Well-Being and Professional Performance amidst Workplace Stressor - Oliquiano, Ailyn; Cuevillas, Rowena (JPAIR Multidisciplinary Research, 2026)
Nurses, who dominate the healthcare profession, become highly exposed to workplace-associate stress. Emotional exhaustion, heavy patient assignment, and absence of support and recognition from health institution, are few factors placing nurses’ own health and quality of care they deliver at risk. The present inquiry aimed to determine the stressors, coping strategies, and the urgency of having structured stress management interventions among nurses in the public hospitals governed by the Provincial Government of Albay. Descriptive-correlational research design was utilized. Two hundred ten nurses (210) from seven public hospitals were surveyed employing total enumeration. The researcher-made validated tool comprised of demographic profiles, stressors assessed using Likert-scale, and checklist on various coping strategies perceived by each nurse. Frequency, weighted mean, and Pearson correlation were used in data analysis. Findings revealed that majority were young nurses, female and under non-permanent contracts. They demonstrated moderate to high levels of work-related stress, with workload and emotional stress as significant contributors. The relationship between stress levels with job status, years of experience, salary range, and number of dependents was robust. Coping strategies were self-initiated and peer-supported. Institutional resources were underutilized. A Nurse Stress Management Program (NSMP) was developed accordingly. The study concludes by observing that workplace stress is an individual and systemic issue, and highlights the imperative for wellness interventions that are age- and context-responsive to enhance nurse resilience and ensure the sustainability of health care.